Genotype-specific root morphology and metabolic traits shape bacterial communities and tolerance to Fusarium root rot in wheat - Omar Hafidi; Marie Simonin; Florent Magot; Yuka Munakata; Alan Kergunteuil; Romain Larbat; Jérémy Grosjean; Alain Hehn; Mathieu Barret; Sophie Slezack (PLoS ONE, 2026)
Plant genotype plays a critical role in shaping root-associated microbiota and in modulating plant tolerance to soilborne diseases such as Fusarium root rot (FRR). In this study, we investigated how four wheat ( Triticum aestivum ) varieties, with differing tolerance to FRR, influence the composition and structure of bacterial communities in the rhizosphere and root endosphere. In the current study evaluated root traits that may contribute to the genotype-specific assembly of bacterial communities across the four wheat genotypes. The variety Concret exhibited the highest FRR tolerance, whereas Pilier was the most susceptible. Analyses of root morphology revealed significant genotype-dependent differences in root length and volume. Notably, traits associated with the tolerant genotype were positively correlated with the abundance of key beneficial bacterial genera in the rhizosphere, including Bacillus , Lysobacter , and Sphingomonas . Untargeted metabolomics identified 879 features, with 20 key metabolites distinguishing the wheat genotypes, including alkaloids, benzoate derivatives, and benzoxazinoid-derived compounds. Correlation analysis revealed significant relationships between these root metabolites and key bacterial taxa. This findings demonstrate that wheat genotypes influence the assembly of the root microbiota through genotype-based morphological and metabolic traits, providing valuable insights into the specific root traits that wheat genotypes can leverage to modulate the plant microbiome and enhance disease resistance.